Turkī meṇ mas̲ẖriq-va-mag̲ẖrib kī kas̲ẖmakas̲ẖ - Ḵẖālida Adīb Ḵẖānum (SAMP early 20th-century Indian books project ;, 1935)
Discusses the struggle between Eastern and Western Milia extension lectures.